Proceso de atención nutricional en paciente masculino de 50 años de edad con hipertensión arterial. - Miranda González, Romina Maite (2023)
The purpose of this clinical case is to improve the blood pressure of a 50-year-old male patient, who lives in the city of Babahoyo, who was diagnosed with hypertension 8 years ago, the same one who is controlled with hypertensive Lozartan, He has a family history of the pathology, he is referred to nutrition due to elevated blood pressure and being overweight. The nutritional care that is given to the patient after the respective information of the anthropometric, biochemical, clinical and dietary assessment data, are to determine the comprehensive nutritional diagnosis and outline the eating plan that provides the diet that provides the macronutrients and covers their needs. energetic. The eating plan will be a low sodium diet with a percentage of 60% carbohydrates, 15% lean protein from white meat, fish and eggs and vegetable protein, in addition to 25% healthy fats in a diet of 2200 kcal/day and divided into 5 meals.